Effect of heat treatment on shore-D hardness of some wood species - Esteves, Bruno (2022)
Hardness is an important wood property for several applications. Typically, it is necessary to use traditional methods, such as a universal test machine, to determine a wood’s hardness value. This work reports the hardness of some wood species before and after heat treatment (ThermoWood method) using the Shore-D hardness method. The Shore- D hardness value of untreated wood ranged between 35.3 for Limba wood and 77.2 for Santos wood. With heat treatment, hardness decreased, and the decrease was greater for samples that underwent harsher treatment (2 h at 212 °C). The decrease of hardness was highest for Sipo wood (14%) and the lowest for Afrormosia wood (2.5%). Analysis of variance tests showed that there was a significant difference between wood species, heat treatment, and the interaction between both variables at the chosen level of significance (P ≤ 0.05). Results showed that Shore-D hardness could be used to measure hardness directly in a production line or in small wood companies without using a universal test machine.